Does dystocia during labor pose a risk factor for another non-progressive labor during the subsequent delivery?. (5th August 2014) - Tobias, Tal; Sheiner, Eyal; Friger, Michael; Sergienko, Ruslan; Harlev, Avi
Abstract: Objective : To establish whether failure to progress during labor poses a risk factor for another non-progressive labor (NPL) during the subsequent delivery. Methods : A retrospective cohort study including singleton pregnancies that failed to progress during the previous labor and resulted in a cesarean section (CS) was conducted. Parturients were classified into three groups for both previous and subsequent labors: CS due to NPL stage I, stage II and an elective CS as a comparison group. Results : Of 202 462 deliveries, 10 654 women met the inclusion criteria: 3068 women were operated due to NPL stage I and 1218 due to NPL stage II. The comparison group included 6368 women. Using a multivariable logistic regression models, NPL stage I during the previous delivery was found as an independent risk factor for another NPL stage I in the subsequent labor (adjusted odds ratio [OR] = 2.9; 95% confidence interval [CI] = 2.4–3.7; p  < 0.001). Similarly, NPL at stage I or II was found to be an independent risk factor for a NPL stage II during the subsequent labor (adjusted OR = 1.4; 95% CI = 1.1–2.1; p  = 0.033; adjusted OR = 5.3; 95% CI = 3.7–7.5; p  < 0.001; respectively). Conclusion : A previous CS due to a NPL is an independent risk factor for another NPL in the subsequent pregnancy and for recurrent cesarean delivery.